Enhancing Payroll Systems for Accountability and User Experience: A Case Study at Kanindo Cooperative, Malang - Ekasari, Kurnia; Afandi, Aang; Yolandra, Aulia Hafida Ade (PT. EQUATOR SINAR AKADEMIA, 2024)
The research aims are to evaluate and develop a payroll accounting information system for the Cooperative Agro Niaga Indonesia Syariah Malang, East Java, which functions as the research object. The analytical approach employs the Business Process Management (BPM) framework, while the system design process employs the ADDIE model. The researcher selected the BPM framework to evaluate the integration of information technology in the accounting information system process more thoroughly. Research is done in five stages. The problem analysis step comes first. At this stage, the information on company issues taken through interviews, documentation, and observational data collection. The second stage involves designing the system using the Business Process Management Notation (BPMN) model and matrix. The third step involves developing a web-based employee payroll accounting information system. The company develops this system to improve the quality of its commercial operations. The implementation stage, which includes evaluation, comes last. This study distinguishes itself by integrating the BPMN framework and ADDIE model to address the complex requirements of payroll accounting systems in a sharia-based cooperative context. Unlike prior studies, this research offers a dual-methodological approach that combines detailed business process visualization with iterative system refinement, ensuring a higher degree of standardization, automation, and user-friendliness. The application in Cooperative Agro Niaga Indonesia Syariah Malang represents a novel contribution by tailoring IT solutions to the unique needs of a rapidly growing sharia financial institution, demonstrating scalability and adaptability for similar organizations.